Analisis Keberhasilan Program Pemberian Obat Pencegahan Massal (POPM) Filariasis Re-TAS 1 di Kabupaten Hulu Sungai Utara: Success Analysis of the Mass Drug Administration (MDA) for Lympatic Program Re-TAS 1 in Hulu Sungai Utara District - Suryatinah, Yuniarti; Rahayu, Nita; Sulasmi, Sri; Yuana, Windy Tri; Setyaningtyas, Dian Eka (Perkumpulan Entomologi Kesehatan Indonesia, 2021)
District of Hulu Sungai Utara conducted an additional 2 (two) rounds of Mass Drug Administration (MDA) for filariasis prevention in 2014 and 2015 that resulted in the success of the re-Transmission Assessment Survey Phase 1 (re-TAS 1) in 2016. This study was conducted to identify factors affecting the technical aspects of the aforementioned two additional rounds of MDA. This is a descriptive qualitative study, with a cross-sectional study design. The research was performed from September to November 2017. Data was collected through in-depth interviews with some executive stakeholders (health workers, cadres, community leaders, local women group) involved in the implementation of MDA for the filariasis elimination program. The result from indepth interviews shows the presence of technical factors at the execution level which supports the smooth implementation of the two additional rounds of MDA. Those factors include communication, resources, operational standard, bureaucracy, and pharmaceutical innovation. The success of the additional MDA rounds was marked by the absence of the re-TAS sample that was tested positive of Brugia Rapid™. The pharmaceutical innovation which transforms the dosage form of the medication into powdered form with some additional sweetener that was done in 2014-2015 can improve coverage of the treatment as well as the medication adherence for the early childhood population group. Changing pharmaceutical dosage forms require additional support in the form of human resources, infrastructure as well as financing.